Strategi Pengajaran Publik Speaking dalam Membangun Kepercayaan Diri Peserta: Wawasan dari Trainer di Makassar - Munadian Yunadia Sahabuddin; Muh. Akbar; Moehammad Iqbal Sultan (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
This article aims to explore the teaching strategies used by public speaking trainers in Makassar City in building participants' confidence, with a focus on strengthening ethos, pathos, and logos as important factors in improving public speaking skills. This study uses a qualitative approach with a descriptive study method, with data collected through in-depth interviews with two main informants, namely Putri Kumalasarisultan and Yudha Prawira Hasta, both of whom are experienced public speaking trainers in Makassar. The results of the study show that the teaching strategies used by both trainers involve experiential learning methods, personal coaching, and the creation of a safe emotional climate to build participants' confidence. Participants' ethos is strengthened through direct experience and personal feedback, while pathos is developed through psychologically supportive classroom design. Participants' logos were strengthened through simulation and role-play techniques that provided real-life speaking experiences and improved their ability to construct logical and structured arguments.